Income distribution and the role of taxation in Philippine development an analysis of two decades - Maertens, Peter (Philippine Journal of Public Administration, 1984)
The comparative analysis of data on income and taxes for the pre- martial law and martial law periods elicited the following trends. The average total family income increased In real terms in the pre-ML period but declined during the ML period. A large number of poor and very poor families both in terms of absolute numbers and percentages graduated to become less poor in the pre-ML period. This trend was reversed during the ML regime when the absolute number of these groups doubled. Based on Gini Coefficients, the Philippines' high inequality ratio lessened in the pre-ML but became very high in the ML period. The data also indicated a very high tax burden of the lowest income group. The Modified Gross Income Tax System was found ineffective in rectifying inequitable tax burden nor in resolving the inadequacy of tax revenues. In sum, taxation had a minimal effect on the nation's distribution patterns.